(3TQM GdaQGFV GdTgGHjIs - (3GdeScQj GdMfaj, YHO GdMdje, J (B900 (3g`s
(3ChdgG (B:s
(3HYO GdHSedI ; hHg fSJYjf (B: (3GdMeO ddg GdYdje GdMcje hGdUdGI hGdSdGe Ydi QShdfG GdcQjes
(3BNQgG (B:s
(3hde jhLO CMO GdePchQjf aGdeGd cdg dHjJ eGd GdeSdejf hGYde Cfg ehdi GdehdGI ebOe Ydi GdebQ dg HGdfSH Ydi GdZjQ HMjK de jKHJ dg HEbQGQg ef Pdc GdZjQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf (B2 / 61s
(3cTa GdXfhf (B2 / 1250s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdaQGFVs